Strategi Brand Activation Ninja Xpress Melalui Special Event - Rusydi Afdillah Fajri (Yayasan Literasi Sains Indonesia, 2025)
Brand Activation is a marketing communication strategy that aims to increase brand awareness, encourage consumer engagement, and build an emotional connection between the brand and customers. This strategy is realized through various forms of activation, such as sponsorship, event organization, social media, promotion, and direct marketing. This study aims to analyze the Brand Activation strategy implemented by Ninja Xpress through Special Event activities, by referring to the Branding Communication theory from Schultz and Barnes. The focus of the analysis includes the influence of the strategy on brand awareness, customer engagement, customer loyalty, brand reputation, sales, and market share. Using a qualitative approach, this study found that programs such as the Master Class Series and Suara UKM Negeri significantly contributed to increasing consumer awareness and positive perception of brands. Interactive activities, the use of social media, and support through sponsorship have proven to be effective in strengthening brand identity and building closeness to the MSME community. The results show that the implementation of the Brand Activation strategy through Special Events by Ninja Xpress has succeeded in strengthening the relationship between brands and consumers, increasing customer loyalty, and encouraging business growth. This holistic approach also provides strategic insight in adjusting marketing and product development according to market needs.